PENGARUH KONEKSI POLITIK DEWAN KOMISARIS DAN KARAKTERISTIK AUDITOR TERHADAP PENGUNGKAPAN HAL AUDIT UTAMA (HAU) (Studi Empiris pada Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Clara Tiffany Setiawan; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of political connections of the board of commissioners and auditor characteristics on the disclosure of Key Audit Matters (KAM) in Indonesia. The dependent variable in this study is the disclosure of Key Audit Matters (KAM). The independent variables consist of the political connections of the board of commissioners, audit committee size, auditor tenure, and client importance to the auditor as representations of auditor characteristics. This study also includes control variables, namely firm size and return on assets (ROA).The sample of this study comprises financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2022 to 2024. The final sample consists of 210 observations. The sample was selected using a purposive sampling method based on predetermined criteria. The data analysis method employed is panel data regression analysis, with the assistance of Eviews 12 software for hypothesis testing.The results of this study indicate that, among the four independent variables tested, only client importance to the auditor has a significant positive effect on the disclosure of Key Audit Matters (KAM). In contrast, audit committee size, political connections of the board of commissioners, and auditor tenure do not exhibit a significant effect on KAM disclosure. These findings suggest that the economic relationship between the client and the auditor plays an important role in determining the extent to which auditors disclose key audit matters in the independent audit report.